Design of an intelligent load feedback system for charging pile in electric vehicles - Zhao, Zhenyu (2021)
As the in dustry becomes more and more developed, the power source as a power source has been paid more and more attention, and the requirements have become higher and higher. At the same time, there are more and more types. The quality assurance of the power supply needs to pass corresponding inspections. As an emerging product, electric vehicle charging piles especially need good quality assurance. General power detection uses fixed resistance or variable resistance to release energy. This traditional method has ma ny shortcomings, such as poor controllability, serious pollution, high power grid power, and easy aging requirements. This method currently cannot meet the current advocates. New requirements for environmental protection, energy saving, and low carbon emis sions. With the development of society, energy saving, emission reduction and new energy vehicles are a general trend. The detection of charging piles is gradually being valued, so the intelligent feedback load of charging piles came into being. The intell igent feedback load can detect the characteristics of charging piles, and at the same time, feed the detected energy back to the grid to realize energy saving and emission reduction during the detection process, save costs for charging pile enterprises and increase product qualification rate. This article divides the intelligent feedback load into a front DC boost DCDC module and a rearstage inverter DC-- stage AC module. The front module adopts the capacitive energy storage type Cuk circuit, and realizend es the detection of the characteristics of the charging pile through the switching of three control modes of constant current, constant voltage and constant power. The backstage inverter module realizes stable control of the DC bus voltage and at the same time controls the gridrelevant standards. connected quality so that the gridconnected current meets the This paper first conducts a theoretical analysis of the frontlevel module, selects a suitable main circuit topology, and then simulates and verifies it through Simulink in MATLAB, and analyzes the simulation waveform; conducts a theoretical analysis of the backlevel inverter module and selects a suitable fullbridge inverse As the main circuit, the variable circuit can stabilize the DC bus voltage an gridd control the connected current at the same time. The overall connection test of the two stages is carried out, and the final result meets the system requirements.